2004
DOI: 10.1111/j.1740-0929.2004.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding methods on eating frustration in stabled horses

Abstract: Five feeding methods were tested in stabled horses: (i) cutting hay (hay was cut into 5 cm lengths), (ii) delaying feeding time (feeding was delayed until 1 h after the usual time), (iii) increasing the feeding frequency (hay was divided into two portions; one half was given at the normal time and the other 1 h later), (iv) increasing the feeding locations (hay was available at three locations), and (v) increasing the hay varieties (three species of hay were used). The behavioral durations in the 2 h after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…The latter behavior is sometimes considered as a reflection of frustration. It seems to be influenced by the motivation to eat and increases after feeding when feeding time is delayed (Hughes and Duncan, 1998;Ninomiya et al, 2004). However, in this study, this result might be related to the experimental setup.…”
Section: Discussioncontrasting
confidence: 72%
“…The latter behavior is sometimes considered as a reflection of frustration. It seems to be influenced by the motivation to eat and increases after feeding when feeding time is delayed (Hughes and Duncan, 1998;Ninomiya et al, 2004). However, in this study, this result might be related to the experimental setup.…”
Section: Discussioncontrasting
confidence: 72%
“…Boissy et al, 2007;Feh and de Mazières, 1993;McBride et al, 2004;Van Den Bos et al, 2003). In contrast, two negative treatments, food competition (FC) and waving of a plastic bag (PB), were hypothesised to result in frustration and fear, respectively (Christensen et al, 2008;König von Borstel et al, 2010;Ninomiya et al, 2004). We have recently demonstrated that these treatments are associated with consistent variation in a measure (angle) of eye wrinkle expression in horses (Hintze et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the stallions, the proportion of concentrate in the diet is much higher, necessary for their special energy requirements for the sport, so they could be more satiated (higher presence of feeding lumps). Moreover, for stabled horses, feeding satisfaction is considered mainly a welfare issue that can be assessed by bed and crib inspection together with after lunch rest behaviour appraisal (Ninomiya et al 2004). For this reason, we have considered the presence of food traces as a housed animal satiety estimator which exhibited the highest OR (14.903).…”
Section: Prevalence Of Welfare Issues On Feedingmentioning
confidence: 99%